Analysis of Histopathological Artifacts in Oral Biopsy Specimen: A Descriptive Cross Sectional Study - Poudel, Pratibha; Adhikari, Bhoj Raj (Journal of College of Medical Sciences-Nepal, 2023)
IntroductionArriving at the final diagnosis requires the histopathological examination of the biopsied lesion. Many a times, diagnosis of lesion may be hindered due to presence of artifacts in the slide. Having a thorough knowledge of these artifacts help to take the precautionary measures to avoid their occurrence. This study is an attempt to analyze histopathological slides from Department of Oral Pathology to identify the artifacts seen in oral biopsy specimens.MethodsThis cross sectional study was conducted in Department of Oral Pathology, Dhulikhel Hospital from July 2021 to February 2022. Slides of all the biopsies during the study period were included in the study. The artifacts were divided into three groups: Artifacts related to surgeons performance, artifacts related to technicians performance and artifacts caused during transfer of sample to the laboratory. Then, the frequency distribution for each type of artifact was calculated.ResultsA total of 280 slides were included in the present study. Artifacts related to technicians performance were seen in 89.3% slides whereas artifacts related to surgeons performance were seen in 76.4% slides. None of the slides showed artifacts related to transfer of sample to the laboratory. The most common artifact seen was eosin leaching (63.6%) followed by stain deposit (60%) and folds and wrinkles (40.7%).ConclusionsThe findings of our study showed that various types of artifacts may be incorporated in biopsy specimen that create difficulty in diagnosing the lesion properly. Proper biopsy protocol and careful handling of sample to prevent technical errors may be helpful to reduce the frequency of artifacts.